2004 International Conference on Power System Technology, 2004. PowerCon 2004.
DOI: 10.1109/icpst.2004.1460156
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for implementing IT support for asset management at electric utilities

Abstract: AbstfudThe last ten to twenty years have seen a steadily growing awareness across industries of the benefits of proper Asset Management, as well gs the obvious disadvantages of poor management of assets. Tbls awareness is specifically apparent in the Power Industry, with an aging infrastructure and workforce coupled with economic pressures enforced by re-regulation and the current economic downturn. Obviously, an apparent tool for utilities seeking to improving efficiency and effectiveness of asset management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The survey [9] showed that the pulp and paper mills had achieved a much tighter integration of their asset-management IT systems, one had implemented a comprehensive CMMS and the other was in the process of implementing it. On the other hand, none of the surveyed utilities utilized a comprehensive CMMS in support of maintenance operation and planning.…”
Section: It Support For Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…The survey [9] showed that the pulp and paper mills had achieved a much tighter integration of their asset-management IT systems, one had implemented a comprehensive CMMS and the other was in the process of implementing it. On the other hand, none of the surveyed utilities utilized a comprehensive CMMS in support of maintenance operation and planning.…”
Section: It Support For Maintenancementioning
confidence: 99%
“…The layout of the survey as well as its results has been reported in [9]. The survey included nine power distribution utilities, one hydropower company, and two pulp and paper mills.…”
Section: B Survey On It Support For Power System Maintenancementioning
confidence: 99%
“…The main functionalities required to manage and process the data in the database are implemented and embedded inside the database itself. Database-centric approach provides usability, offers various indexing and query capabilities, and provides many basic processing operations through an easy-to-use and standard interface [31].…”
Section: B Linking Smart Grid Business Domains To Integration Technimentioning
confidence: 99%
“… Strategies for Implementing IT support for Asset Management at electric utilities (Jonsson, et al, 2004): está investigación realizó un análisis sobre las estrategias empleadas con base en la gestión de activos, para encontrar oportunidades de mejora en centrales eléctricas e industrias de pulpa y papel.…”
Section: Asset Managementunclassified